TÜRKİYE'DE OKUL KÜTÜPHANELERİNİN HİZMET VERMESİNİ ETKİLEYEN YÖNETİMSEL FAKTÖRLER - H. İnci Önal (Türk Kütüphaneciliği)
The management factros effecting the services of school libraries are educational poMcy, principles of management, organization and funçtions, rules and regulations. This study undertakes the analysis of these factors in realiton to }the school library deve/opment in Turkey.